The Effectiveness of Exclusive Breastfeeding on the Nutritional Status of Infants in Efforts to Prevent Stunting in PMB Bogor Regency - Rochmawati, Rochmawati; Kusmintarti, Arini (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Breast milk contains all the nutrients needed by the body, evidenced by the results of scientific evidence about the benefits of breast milk for the baby's immune system, growth and development, babies who are not exclusively breastfed have a higher risk of disease. The purpose of the researcher is to discuss further about the effect of exclusive breastfeeding on the nutritional status of infants aged 6 months at PMB Dian Dwi Anggraini, Bogor Regency 2022. The observational research design is analytical, cross-sectional with purposive sample sampling, data analysis comparison of independent variables with dependent variables, with independent T-Test statistical tests. Based on the results of independent T-test analysis in the study, the average body weight of exclusively breastfed infants (6.03 kg) and non-exclusive breastfeeding (5.57 kg) was obtained, while the average body length was obtained from exclusively breastfed infants (59.0 cm) and in non-exclusively breastfed infants (57.92 cm), for nutritional status in exclusively breastfed infants obtained 0.14 (Z score) and Non-exclusive breastfeeding 0.97 (Z score). This shows that exclusive breastfeeding affects the nutritional status of infants who are exclusively breastfed and those who are not exclusively breastfed very significantly with a p-value of > 0.01.